The Effects of Communication Skills Training on Dental Students' Clinical Empathy - soheila Derisavy Jorfian; nahid Ahmadian Yazdi; amir Daneshpayeh (Babol University of Medical Sciences, 2023)
Background and Objective: Empathy between dentists and patients increases patient satisfaction and the effectiveness of dental treatments. With more empathy, dentists find more competence in taking history, performing clinical examinations and need assessment and treatment plans and giving instructions after treatment, and getting the cooperation of their patients. Research has shown that students' empathy decreases during their studies. Methods: 60 students completed the Jefferson Clinical Empathy Questionnaire. Students were randomly assigned to two intervention and control groups of 30 people. The workshop was held for the group. After one month, the clinical empathy questionnaire was completed again by both groups. The questionnaire information of both groups before and after the workshop was entered into SPSS version 21 software and analyzed.  Findings: There was no statistically significant difference between the intervention and control groups regarding demographic and educational variables. Also, the average score of Jefferson's empathy in the two groups before the intervention was not statistically significant (P=0.76). However, after holding the training program for the case group, a statistically significant difference was found in the clinical empathy score of the case group and the control group (P=0.03). Also, the difference in the mean empathy score of the case group before and after the intervention was significant (P=0.05). Except for the ethnicity variable (P=0.03), none of the demographic variables had a significant relationship with the empathy score after the intervention. Conclusion: By teaching communication skills, the level of clinical empathy of dental students can be improved.